2003
DOI: 10.1161/01.str.0000068170.80517.b3
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Plus Caffeine (Caffeinol) for Treatment of Ischemic Stroke

Abstract: Background and Purpose-Ethanol and caffeine are 2 common psychoactive dietary components. We have recently shown that low-dose ethanol plus caffeine results in a 70% to 80% reduction of infarct volume after reversible common carotid/middle cerebral artery (CCA/MCA) occlusion in rats. The combination (caffeinol) was effective after either oral pretreatment or intravenous administration starting up to 2 hours after stroke onset. Ethanol alone aggravated ischemic damage, while caffeine alone was without effect. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 26 publications
2
56
0
1
Order By: Relevance
“…This has sometimes been referred to as the "cocktail" approach [1,39]. With the use of multiple neuroprotective therapies, each agent could be given either simultaneously or in rapid succession, allowing each agent to work on a different ischemic injury mechanism [2,3,5,7,8,17,26,29,32]. Therefore we suggest that a "combotemporal stroke therapy", such as the combined use of a neuroprotective or anti-inflammatory agent and an excitatory amino acid antagonist simultaneously or in sequence, may provide greater neuroprotection than either agent alone.…”
Section: Discussionmentioning
confidence: 99%
“…This has sometimes been referred to as the "cocktail" approach [1,39]. With the use of multiple neuroprotective therapies, each agent could be given either simultaneously or in rapid succession, allowing each agent to work on a different ischemic injury mechanism [2,3,5,7,8,17,26,29,32]. Therefore we suggest that a "combotemporal stroke therapy", such as the combined use of a neuroprotective or anti-inflammatory agent and an excitatory amino acid antagonist simultaneously or in sequence, may provide greater neuroprotection than either agent alone.…”
Section: Discussionmentioning
confidence: 99%
“…TPA with caffeinol imparts no increased risk of intracranial hemorrhage in vivo, and no reduction of TPA fibrinolytic activity in vitro. 213 The protective effect of caffeinol has recently been confirmed in the suture model of transient MCA occlusion, with the predominant effect on cortical salvage. The protective mechanism is likely due to the synergistic effect of caffeine and ethanol on the excitatory/inhibitory balance between neurotransmitter systems.…”
Section: Caffeinolmentioning
confidence: 94%
“…213 In this model, hypothermia was started 60 min after the onset of ischemia and continued for 240 min. A pilot study designed to establish the feasibility and safety of administering both caffeinol and mild systemic hypothermia in acute ischemic stroke patients treated with i.v.…”
Section: Caffeinolmentioning
confidence: 99%
“…Aronowski et al, 3 utilizing a rat model of common carotid artery/left MCA infarct, treated different cohorts with combinations of ethanol, caffeine, and hypothermia. They concluded that low doses of caffeine, equivalent to 2-3 cups of coffee, and low doses of ethanol, equivalent to 1 cocktail, are highly neuroprotective and can reduce cortical infarct volumes and behavioral dysfunction after transient occlusion.…”
Section: Caffeinol (Caffeine and Ethanol)mentioning
confidence: 99%